Estudio ergonómico para identificar las enfermedades profesionales a cuñeros y encuelladores de la industria petrolera en taladros de reacondicionamiento en la empresa Triboilgas CÍA. LTDA, en la región oriental del Ecuador; crear un plan de acción en fución de los resultados obtenidos. - Villamarín Carrera, Luis Roberto (2015)
The present investigation carried out at the Triboilgas Oil Service Enterprise Cia. Ltda. Was aimed at forewarning workers health by means of an ergonomic study to cuñerps and encuelladores since these positions are the ones that require most of the physical effort in the reconditioning of oil wells. Since science and workers care have been developed notably in the last 20 years due to the implementation of laws, standards and statutes to avoid professional sicknesses and at-work accidents which influence in family and working settings; different methods are analyzed in order to employ the most appropriate method on evaluating ergonomic risk; the most renown methods: RULA, OWAS, REBA, NIOSH and G-INSHT; Once the activity that involves most of the risk and exposure for the cuñero and encuellador, the method that will be used en the evaluation, according to the obtained results, an action plan is elaborated for the benefit of the enterprise workers, the Ecuadorian working society which will benefit many professionals of the security field and occupational health to carry out projects related to the topic in order to take care of human talent which is the motor of every institution